Dryland land-use conflicts in humid tropics: an analysis using geographic information systems and land capability evaluations - Risma Neswati; Sumbangan Baja; Samsu Arif; Hasni Hasni (Universitas Sebelas Maret, 2020)
This study analyses land-use conflicts in specific dryland agricultural areas in relatively dry humid tropics based on the Regional Spatial Land Use Planning Regulations and land-capability evaluation. This research was conducted in the Regency of Jeneponto, South Sulawesi, Indonesia. The observation site was chosen based on several maps overlapping to produce 30 land units spread across 14 land systems in Jeneponto. This study integrates ground surveys and geographic information systems technology. The land capability analysis used a simple approach factor, according to United States Department of Agriculture definitions. The results indicate that land capability was dominated by Class IV, which covered 35,133 ha or 63.1%. Class VI covered 12,581 ha or 22.6%, Class III covered up to 4,378 ha or 7.9%, and Class VIII covered 3,130 ha or 5.6%. Class VII covered only 486 hectares, or 0.9%, the smallest area. These results indicate that the dryland area which had become a land-use conflict was delineated by Regional Spatial Land Use Planning Regulations. The drylands found in Jeneponto cover 22,214 ha or 39.9%, which has been divided into two: an area where non-dryland agriculture was converted into dryland farming (16,503 hectares, or 29.6%), and an area where dryland-farming was converted into non-agricultural dryland area (5,711 hectares, or 10.3%). Interviews with 50 farmers in the study location revealed factors that had changed agricultural dryland use into non-agricultural dryland use; lower incomes due to decreased soil fertility was a crucial factor.